Authenticity and Commodification of Creative Industry Products in The Tourism Sector, Bali - Dewa Putu Oka Prasiasa; Dewa Ayu Diyah Sri Widari; Putu Herny Susanti (Mudra Jurnal Seni Budaya, 2023)
The creative industry places an emphasis on the creativity of a product, the understanding that the creator is known and has a copyright. In addition, the creative industry has links with the cultural industry, because its products are components of culture. When market tastes lead to post-industry, it is found that creative industry products consumed by tourism experience a change from homogeneous to heterogeneous with mass production. Changes in market tastes encourage the emergence of highly varied creative art products, as a result of the creative economy industry. The entry of the creative economy industry into the realm of culture, which then develops into the cultural industry, apart from growing the local and national economy, also has an impact on cultural components, especially from the aspects of authenticity and commodification. The areas affected include performing arts, tourism, entertainment, fashion, craft products, and culinary. In order to increase the competitiveness of Indonesian tourism, especially from the cultural pillar, the aspects of authenticity and commodification can increase its contribution to the local and national economy through the implementation of internationalization, traditionalization, and sacred versus profane.